In situ surface X-ray diffraction study of ultrathin epitaxial Co films on Au(111) in alkaline solution. (10th April 2016) - Reikowski, Finn; Maroun, Fouad; Di, Nan; Allongue, Philippe; Ruge, Martin; Stettner, Jochim; Magnussen, Olaf M.
Abstract: The oxidation behavior of ultrathin electrodeposited Co films on Au(111) in alkaline electrolyte was studied using in situ surface X-ray scattering techniques employing synchrotron radiation and complementary optical reflectivity and electrochemical measurements. The films are formed at pH 4 and consist of (001)-oriented hcp Co crystallites that are several nm high, a few ten nm in diameter, and remain largely unchanged after electrolyte exchange to pH 12 solution. In the pre-oxidation peak only minor changes were observed in the diffraction studies, excluding the formation of Co(OH)2 layers. In the potential regime of Co hydroxide formation a rapid reduction of the amount of Co is observed, while the characteristic height of the islands decreases only slightly. On longer times scales, growth of 3D crystals of Co(OH)2 occurs as well as irreversible Co dissolution into the electrolyte is found. On the basis of the structural observations oxidation of the Co film is proposed to proceed via fast formation of an ultrathin passivating layer, followed by nucleation and growth of 3D hydroxide crystals at the grain boundaries in the Co deposit.